Influence of Surface Properties of Filtration-Layer Metal Oxide on Ceramic Membrane Fouling during Ultrafiltration of Oil/Water Emulsion - Lu, D.; Zhang, T.; Gutierrez, L.; Ma, J.; Croué, Jean-Philippe (American Chemical Society, 2016)
In this work, ceramic ultrafiltration membranes deposited with different metal oxides (i.e., TiO2, Fe2O3, MnO2, CuO, and CeO2) of around 10 nm in thickness and similar roughness were tested for O/W emulsion treatment. A distinct membrane fouling tendency was observed, which closely correlated to the properties of the filtration-layer metal oxides (i.e., surface hydroxyl groups, hydrophilicity, surface charge, and adhesion energy for oil droplets). Consistent with the distinct bond strength of the surface hydroxyl groups, hydrophilicity of these common metal oxides is quite different. The differences in hydrophilicity consequently lead to different adhesion of these metal oxides toward oil droplets, consistent with the irreversible membrane fouling tendency. In addition, the surface charge of the metal oxide opposite to that of emulsion can help to alleviate irreversible membrane fouling in ultrafiltration. Highly hydrophilic Fe2O3 with the lowest fouling tendency could be a potential filtration-layer material for the fabrication/modification of ceramic membranes for O/W emulsion treatment. To the best of our knowledge, this is the first study clearly showing the correlations between surface properties of filtration-layer metal oxides and ceramic membrane fouling tendency by O/W emulsion.